Meaning and experiences in managing primary education development programme school funds among public primary schools head teachers in Tanzania - Mwinjuma, Juma Saidi; Abdul Kadir, Suhaida; Hamzah, Azimi; Basri, Ramli (Human Resource Management Academic Research Society, 2017)
The main purpose of the study was to understand the meaning and experiences of primary schools head teachers in managing Primary Education Development Programme (PEDP) funds. Data was collected using semi-structured interviews with head teachers at public primary schools. Seven informants were selected from a number of schools based on educational attainment and experience serving as a head teacher. Interviews were recorded, transcribed verbatim and analysed systematically. Direct school funding has only offered limited solutions to resources acquisition in schools due to availability of insufficient funds in schools. Secondly, schools do not have full autonomy to use the allocated funds to fulfil locally determined school requirements. Thirdly, at school levels there is a state of confusion between participatory decision making and the issue of taking responsibilities. Fourthly, there is a need and urgency to build their capacities through continuous trainings. Based on these conclusions, the study recommends for systemic approach to understanding allocation of PEDP funds in order to improve quality of education in public primary schools in Tanzania. Finally, for head teachers and other stakeholders to act and facilitate effective implementation of educational programmes such as PEDP, there is a need and urgency to build their capacities to competently manage these educational programmes.